Incidencia del déficit de atención en el proceso de enseñanza aprendizaje en los estudiantes de los 8° años de educación general básica de la unidad educativa “Ramón Páez” ubicada en la parroquia Eloy Alfaro, cantón Latacunga, provincia de Cotopaxi - Yauli Toapanta, Carmen Cecilia (2015)
Actually the educational reality is affected by the low academic performance of students in different knowledge areas, this the reason because this research has as main objective to determine the attention impact deficit in the teaching learning process, since a teacher must have a good training for working with students that have some problems to learn in all areas of education, it means this research will be a good guide to help teachers to reach their aim of form students with critical and reflective character able to develop by themselves in the actual society, so it is vital important the implementation of a didactic guide for teachers, the same that will be directed to help and guide students who present learning problems because of their lack of attention in the teaching learning process….